Impact of oil waste discharge from Al-Nassiriya oil refinery upon physical chemical properties and heavy elements content of vicinity soil - Bassim y. AL-khafaji; Noora Q. Kareem (University of Thi-Qar Journal of Science, 2021)
The present study attempt to know the impact of oil waste discharge from Al-Nassiriya oil refinery upon some physical chemical properties and heavy elements (HEs) concentration in the vicinity soil , during the period from January until August 2020 . Some physical and chemical factors were measured also selected HEs ( Co , Ni , Pb and V ) concentration in the soil were measured by using Flam Atomic Absorption Spectrometry ( FAAS ) , in addition to soil texture and total organic carbon content were measured as percentage . The results revealed that the range of the soil parameters were , Temp.(16.3 – 44.3) ◦c , pH (6.0 - 8.7) , electrical conductivity E.C. (119.2-312.10) µs/cm , salinity (0.02 - 1.63) gm/kg , porosity (29 – 58) % , NO3 (7.91 - 97.5) mg /kg , PO4 (5.4 - 24.7) mg/ kg , SO4 (480 - 1739) mg/kg , while soil texture was silty clay at st.1 and st.2 , sandy loam at st.3 and silty loam at st.4 . Total organic carbon (TOC %) content and organic matter (OM%) were ranged from (3.89 - 17.52) % and (2.26 – 10.16) % respectively . HEs content in the soil of study were ranged from Pb (5.9 - 63.7 ) , Co (4.7 - 51.77) , V (36 - 181 ) and Ni (5.57 - 222 ) mg/kg dry weight respectively .